2006
DOI: 10.1007/s00024-006-0080-8
|View full text |Cite
|
Sign up to set email alerts
|

Depth Estimation from Gravity Data Using the Maximum Entropy Method (MEM) and the Multi Taper Method (MTM)

Abstract: The depth determination from the gravity data in frequency domain is carried out using the classical fast Fourier transform (FFT) method utilizing scaling properties of ensemble of anomalous source. The problem of calculating power spectrum from the FFT is well described in the literature. Here, the application of other high-resolution methods of power spectrum calculation, such as maximum entropy method (MEM) and multi-taper method (MTM) are explored to estimate depth to anomalous sources. At the outset, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…This difference in correlation is possible because different methods give different values of scaling exponents. The higher correlation for the MTM may be due to more reliable values of scaling exponents by this method (McCoy et al, 1998;Bansal et al, 2006). These values of the correlation coefficients indicate significant influence of fracture density and conversion log on the values of the scaling exponents.…”
Section: Comparison Of Scaling Exponents With Fracture Density and Comentioning
confidence: 79%
See 1 more Smart Citation
“…This difference in correlation is possible because different methods give different values of scaling exponents. The higher correlation for the MTM may be due to more reliable values of scaling exponents by this method (McCoy et al, 1998;Bansal et al, 2006). These values of the correlation coefficients indicate significant influence of fracture density and conversion log on the values of the scaling exponents.…”
Section: Comparison Of Scaling Exponents With Fracture Density and Comentioning
confidence: 79%
“…Details about the multitaper method and discrete prolate tapers may be found in Percival and Walden (1993). The MTM is found to be superior as compared to the periodogram and maximum entropy method (MEM) for computing the scaling exponents (McCoy et al, 1998) whereas Bansal et al (2006) found MTM more suitable for finding the depth of sub-surface structures using the scaling spectral method.…”
Section: Power Spectral Density Estimation: Fast Fourier Transform (Fmentioning
confidence: 93%
“…Among various spectral analysis methods, the multitaper method is a high-resolution and superior technique (PERCIVAL and WALDEN, 1993) in comparison to the fast Fourier transform (FFT) method and maximum entropy method for estimating the mean depth of the interfaces from gravity data (BANSAL et al, 2006). Here, the multitaper method is applied to the Bouguer anomaly data across the NW Himalaya.…”
Section: Spectral Analysismentioning
confidence: 99%
“…The spectral analysis method has been widely used to determine the depth to the top of magnetic source bodies without any prior knowledge of the geometry from the wavelengths of potential fields (Bhattacharyya 1966;Bhattacharyya andLeu 1975, 1977;Bansal and Dimri 2001;Bansal et al 2006;Chavez et al 1999;Curtis and Jain 1975;Gomez-Ortiz et al 2005;Hofstetter et al 2000;Lefort and Agarwal 2002;Nnange et al 2000;Pal et al 1979;Pamukcu et al 2007;Poudjom Djomani et al 1992;Rivero et al 2002;Spector and Grant 1970). This method for estimating the mean depth to ensembles of magnetic sources has been generalized to gravity data (Dimitriadis et al 1987) and can be used to map geologic structures from gravity and/or magnetic data observed at the earth's surface (Treitel et al 1971).…”
Section: Spectral Analysis Methods and Crustal Structurementioning
confidence: 98%